Fuel Demand Elasticities in Brazil: A Panel Data Analysis with Instrumental Variables - UchÃ´a, Frederico; de Jesus, Cleiton Silva; Cardoso, Leonardo Chaves Borges (International Journal of Energy Economics and Policy, 2020)
The aim of this paper is to provide demand elasticities for the three main fuels used in Brazil: gasoline, ethanol and diesel. We used a panel data approach at municipal level for the period between 2007 and 2016. The innovation in this study is in its introduction of a new instrumental variable for prices, combining three taxes and municipal distance from state capital. The main results are as follows: i) the gasoline, ethanol and diesel demands are price elastic, meaning that all own-price elasticities are greater than one; ii) ethanol consumption is more elastic when the CNG price is added as an explanatory variable, but this does not apply to gasoline; iii) an increase in GDP positively affects the demand for gasoline and diesel (less than proportionally), but does not affect demand for ethanol; iv) fleet size impacts the consumption of all fuels, except when the CNG price is excluded from the ethanol model; v) the ethanol-to-gasoline price ratio is a relevant variable for the demand of both gasoline and ethanol. Keywords: Fuel demand, Causal inference, Panel data analysis, price elasticity, cross price elasticity. JEL Classifications: C13, C26, L11, Q41, Q2. DOI: https://doi.org/10.32479/ijeep.8787